CT head reporting by radiographers: Results of an accredited postgraduate programme. Issue 3 (August 2015) - Lockwood, P.; Piper, K.; Pittock, L.
Abstract Aim To evaluate the results of the summative objective structured examination (OSE) for the first four cohorts of radiographers (n = 24) undertaking an accredited postgraduate course in reporting computer tomography (CT) head examinations. Method The construction of a summative OSE contained twenty five CT head examinations that incorporated 1:1 normal to abnormal pathological examples. All cases were blind reported by three consultant radiologists to produce a valid reference standard report for comparison with the radiographer's interpretation. The radiographers (n = 24) final reports (n = 600) were analysed to determine the sensitivity, specificity and agreement values and concordance for the four cohorts. Results The four cohorts (2007–2013) of postgraduate radiography students' collective OSE results established a mean sensitivity rate of 99%, specificity 95% and agreement concordance rates of 90%. The final grades indicate that within an academic environment, trained radiographers possess high levels of diagnostic performance accuracy in the interpretation of CT head examinations.